Effectiveness of predictive markers for marker assisted selection of pro-vitamin A carotenoids in medium-late maturing maize (Zea mays L.) inbred lines - Gebremeskel, S.; García Oliveira, A.L.; Menkir, A.; Adetimirin, Victor O.; Gedil, Melaku A (Elsevier, 2018)
Development of pro-vitamin A (PVA) biofortified staple crops has been promoted as an option for addressing vitamin A deficiency in humans. Recently, crtRBI, lcyE and zep1 genes of carotenoid biosynthesis pathway have been identified as contributors to PVA accumulation in maize endosperm. High phenotyping cost and narrow genetic base for these nutritionally important compounds have been regarded as the major challenges. We evaluated the fidelity of existing functional markers along with new markers for PVA carotenoids and assessed the diversity of 108 maize inbreds using SSR markers. Among the existing markers, crtRB1-5′TE and crtRB1-3′TE exhibited highly significant association with PVA whereas marker Zep-SNP(801), developed in this study, was associated only with α-carotene. Collectively, a substantial improvement in the PVA content, including β-carotene, was observed with increased number of total favourable alleles. Cluster analysis based on SSR produced two major groups, each with three and two sub-groups, respectively. The inbreds containing favourable alleles of the functional markers were present in all sub-groups. Finally, this genetically diverse inbreds with high PVA can be used in breeding programme using marker-assisted selection to enhance PVA content in maize hybrids and cultivars developed for lowlands in sub-Saharan Africa.